Political participation in the Internet age: factors and conditions - Avzalova, Elmira I. (Opción, 2019)
The application of the system approach and the structural and functional method allowed the forms of Internet participation of citizens in politics, the main factors and conditions determining the possibility of participation of citizens in politics through the Internet to reveal. As a result, the most important areas of legislative regulation should be the provisions of free dissemination of information, including information on the activities of public authorities. We can conclude that an important condition for Internet participation of citizens in the political process stemming from the peculiarities of the regime is the position of the political elite.